EFFECT OF QUICK RESPONSE CODE ON AGRI FOOD CONSUMPTION - Ignjatijević, Svetlana; Vapa Tankosić, Jelena; Krstić, Snežana; R. Bojić, Marko; Medić, Zorica (Economics of Agriculture, 2020)
By adopting a quantitative research methodology this paper seeks to explore the characteristics and applicability of the QR codes in agri-food products. The research was conducted in Serbia with a sample 308 respondents. The statistical analysis methods employed were correlation and factor analysis using SPSS statistical program. The findings indicate that younger, more educated population in the proposed content of the QR code of honey; value the information on the certificate of honey quality, the chemical composition of honey and the influence of honey ingredients on the body with information on how to identify real honey, in relation to counterfeit, as the most useful to consumers. The results of this research have been further applied for the development of a QR code for a traditional food product, the Fruška Gora linden honey with a geographical indication.